Measurement of CP violation in B0→J/ψK0S - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; et al. (Physical review letters, 2015)
Measurements are presented of the CP violation observables S and C in the decays of B0 and ¯B0 mesons to the J/ψK0S final state. The data sample corresponds to an integrated luminosity of 3.0 fb−1 collected with the LHCb experiment in proton-proton collisions at center-of-mass energies of 7 and 8 TeV, and contains a total of 41 560 selected B0 and ¯B0 decays. The analysis of the time evolution of these decays yields S=0.731±0.035(stat)±0.020(syst) and C=−0.038±0.032(stat)±0.005(syst). In the standard model, S equals sin(2β) to a good level of precision. The values are consistent with the current world averages and with the standard model expectations.
Im Titel ist "0" hochgestllt und "S" tiefgestellt, wobei "S" unter "0" steht
LHCb Collaboration: R. Aaij, B. Adeva, M. Adinolfi, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, U. Uwer, M. Vesterinen, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 668 weitere]
Gesehen am 07.07.2021